Being San' in Platfontein: Poverty, landscape, development and cultural heritage - Soskolne, Talia (Social Anthropology, 2014)
As people are relocated, dispossessed of land, or experience the altered landscapes of modernity, so their way of life, values, beliefs and understandings are transformed. For the !Kun and Khwe people living on Platfontein this has been an ongoing process. Platfontein, a dry, flat piece of land near Kimberly in the Northern Cape, was purchased for the Kun and Khwe through the provision of a government grant in 1997. They took permanent residence there in government-built housing in December 2003. Prior to this they had had numerous experiences of relocation and strife, through a long-term involvement with the SADF that brought them from the Omega army base in Namibia, to a time of uncertainty in the tent town of Schmitsdrift, to their current settlement on Platfontein. The dry barren landscape of Platfontein suggests a very different way of life from that of hunter-gathering in Angola and Namibia. In the semi-urban context of Platfontein, basic sustenance and entry into the job market are emphasized, and this brings about changes in people's way of life and understandings, as well as in how they relate to each other and the landscape. In this context, there are certain tensions and contradictions that underlie the work of social development and cultural heritage that are the mandates of SASI (South African San Institute) in Platfontein. It is essential that projects initiated by NGOs like SASI give cognizance to the complexities of people's lives, histories and story lines. Without this, people's experiences and multifaceted stories are inevitably sidelined to create essentialist narratives that meet the imaginings of tourists and sponsors. There is no doubt that SASI works from an intention of bringing about positive transformation in Platfontein, and has done useful work in the community. The essentialist discourse of the 'indigenous', however, is a ready temptation for NGOs and the groups they represent to adopt, as it is politically expedient to do so in order to gain access to land and resources. This needs to be challenged at the level of policy so that access to geographical space or political power does not necessitate a denial of history or complexity.